Keunggulan produk lokal sebagai mediasi dalam hubungan orientasi pasar dan kinerja pemasaran usaha kecil dan menengah - Tatang Rois; Fauziyah Adzimatinur; Nurul Siti Jahidah (Jurnal Manajemen Maranatha, 2026)
The differences in previous studies related to the influence of market orientation on marketing performance, the scarcity of studies on local products, and the challenges faced by SMEs in improving marketing performance, form the basis for this further research. This study aims to examine the role of local product advantage as a mediating variable in the relationship between market orientation and marketing performance. This study was conducted empirically on SMEs engaged in the processing of local products typical of Kuningan Regency. The sampling technique used was disproportionate random sampling with a total of 200 respondents. Data analysis was performed using the Structural Equation Modelling (SEM) approach. The findings show that both market orientation and local product advantage have a significant effect on marketing performance, and local product advantage has been proven to mediate the relationship between market orientation and marketing performance. Theoretically, these results reinforce the concept of market orientation, enrich the literature on local products, and clarify the inconsistencies in previous studies. The practical implications for SMEs include applying differentiation strategies based on local characteristics, strengthening context-appropriate market orientation, and enhancing internal organisational capabilities.